Penerapan terapi spiritual dzikir terhadap tingkat kecemasan pasien diabetes mellitus - Marliyana, Marliyana; Fitri, Feni Elda (JOURNAL OF Tropical Medicine Issues, 2025)
Background: Diabetes mellitus is a systemic, cronic and multifactoral disease characterized by hyperglycemia and hyperlipidemia. Symptoms that arise are a result of lack of insulin secretion or the presence of adequatte but ineffective insulin. Diabetes mellitus is often associated with disorders of the microfaskulkar and macofascular systems, neuropathic disorders, and lesidermopathatics. Patients with diabetes mellitus have complications of anxiety syndrome, and also show a correlation between diabetes mellitus and anxiety. One of the non-pharmacological therapies to reduce anxiety is dzikir spiritual therapy. Purpose: To determine the level of anxiety in patients with diabetes mellitus before and after the dzikir spiritual therapy. Method: The type of scientific paper used is descriptive by using the case study approach method. The subjects in this scientific paper are two people who have diabetes mellitus with anxiety problems. Retrieval of scientific writing data at the Beringin Raya Health center Kemiling Bandar Lampung. Results: Scientific papers show that there was a decrease in anxiety scores before and after being given dzikir spiritual therapy. Conclusion: Dzikir spiritual therapy as an independent exercise in patients with diabetes mellitus that can be done every day after prayer to reduce anxiety levels. Keywords: Anxiety; Diabetes; Spiritual Dzikir. Pendahuluan: Diabetes mellitus merupakan penyakit sistemis, kronis, dan multifaktoral yang dicirikan dengan hiperglikemi dan hiperlipidemia. Gejala yang timbul adalah akibat dari kurang sekresi insulin atau adanya insulin yang cukup tetapi tidak efektif. Diabetes mellitus sering kali dikaitkan dengan gangguan sistem mikrofaskulkar dan makofaskular, gangguan neuropatik, dan lesidermopatik. Pasien dengan diabetes mellitus memiliki komplikasi sindrom kecemasan, dan juga menunjukkan adanya korelasi diabetes mellitus terhadap kecemasan. Salah satu terapi non farmakologi untuk menurunkan kecemasan salah satunya adalah terapi spiritual dzikir. Tujuan: Untuk mengetahui tingkat kecemasan pada pasien diabetes mellitus sebelum dan sesudah dilakukan tindakan terapi spiritual dzikir. Metode: Jenis karya tulis ilmiah yang digunakan adalah deskriptif dengan menggunakan metode pendekatan studi kasus. Subyek dalam karya tulis ilmiah ini adalah dua orang yang mengalami diabetes mellitus dengan masalah kecemasan. Hasil: Pengambilan data karya tulis ilmiah di Puskesmas Beringin Raya kemiling Bandar Lampung. Hasil karya tulis ilmiah menunjukkan bahwa adanya penurunan skore kecemasan sebelum dan sesudah diberikan terapi spiritual dzikir. Simpulan: Latihan terapi spiritual dzikir sebagai latihan mandiri pada pasien diabetes mellitus yang bisa dilakukan setiap hari sesudah sholat untuk menurunkan tingkat kecemasan. Kata Kunci: Diabetes; Kecemasan; Spiritual Dzikir.